Acute high-altitude sickness - Luks, Andrew M.; Swenson, Erik R.; Bärtsch, Peter (European respiratory review, 2017)
At any point 1–5 days following ascent to altitudes ≥2500 m, individuals are at risk of developing one of three forms of acute altitude illness: acute mountain sickness, a syndrome of nonspecific symptoms including headache, lassitude, dizziness and nausea; high-altitude cerebral oedema, a potentially fatal illness characterised by ataxia, decreased consciousness and characteristic changes on magnetic resonance imaging; and high-altitude pulmonary oedema, a noncardiogenic form of pulmonary oedema resulting from excessive hypoxic pulmonary vasoconstriction which can be fatal if not recognised and treated promptly. This review provides detailed information about each of these important clinical entities. After reviewing the clinical features, epidemiology and current understanding of the pathophysiology of each disorder, we describe the current pharmacological and nonpharmacological approaches to the prevention and treatment of these diseases.